The Benefit of Purple Aruk Rice (Siangu) in Lowering Body Mass Index (BMI) and Body Fat Percentage - Rini Arianti; Oktarina Oktarina (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2018)
Aruk rice is an iconic rice from Province of Bangka Belitung which is made from cassava while purple aruk rice (PAR)e is made from sweet potato (Ipomea batatas). Ipomea batatas is a high nutritional food that possesses several medicinal value including anti-cancer, antidiabetic, and anti-inflammatory activities. This research aimed to assest the organoleptic features of PAR and analyze the effect of PAR consumption in lowering the BMI and bofódy fat percentage. The design of this research was randomized crossover design with quasi experimental research within subjects single-factor two-level design. This experiment consist of three phases, phase 1 (plain rice consumption), wash out phase, and phase 3 (PAR consumption). The only different between two phases was the source of the carbohydrate. The data of decreasing BMI and body fat percentage betweern plain rice diet and purple aruk rice was analyzed by using paired t test. Organoleptic assessment showed that the aroma of PAR is dislikeable but the natural purple colour is likeable. The decreasing of BMI and body fat percentage was found higher in phase 2 (2,05±0,10) than phase 1 (0,4±0,14), p=0,002. The decreasing of body fat percentage was also found higher in phase 2 or purple aruk rice diet (2,55±0,25) compared to phase 1 plain rice diet (0,5±0,20), p=0,003. Consumption of aruk purple rice lower BMI and body fat percentage more effective than consumption of plain rice.